Application of chitosan-based coatings on frozen salmon - Sensory assessment and retail simulation approach - Silva, Pedro Miguel Peixoto da (2017)
GLUPOR 12 - 12nd International Meeting of the Portuguese Carbohydrate Chemistry Group